Global Issues in Digital-Based Education Marketing for World Class Education at Universitas Internasional Batam - Agung Setiabudi; Kasful Anwar Us; Fridiyanto; Sri Kadarsih (Future Techno-Science, 2026)
This study explores the global digital marketing strategies implemented by Universitas Internasional Batam (UIB) in its pursuit of World Class Education (WCE). Employing a qualitative descriptive approach, the research analyzes UIB’s efforts to expand its international reach through multilingual website development, participation in global mobility programs such as Erasmus and AIESEC, and active digital campaigns across social media platforms. Findings reveal key challenges including limited multilingual content, insufficient digital marketing infrastructure and human resources, and a lack of differentiated international academic programs and sustainable collaborations. Despite these challenges, UIB demonstrates strategic progress through capacity-building initiatives, accreditation efforts, and enhanced global partnerships. The study highlights the importance of integrating digital innovation with local cultural values (glocalization), strengthening international academic networks, and adopting data-driven marketing approaches. The results provide valuable insights for higher education institutions aiming to compete effectively in the increasingly globalized digital education market.